Interfacial defects on mixed matrix membranes and mitigation techniques for gas separation: A review - Shimekit, B. (Trans Tech Publications Ltd, 2014)
Development of novel mixed matrix membranes (MMMs) has become frontier candidates for improving the upper bound trade-off curve between permeability and selectivity of gases for industrial polymeric membranes. However, fabrication of ideal MMMs is practically challenging as the dispersion of inorganic phase into the polymer may produce polymeric-inorganic interfacial defects at the vicinity of the polymer matrix. For instance, the inorganic phase may cause interfacial void, polymer chain rigidification or partial pore blockage on the overall MMMs. Since there are only few studies that specifically focus on the issues of the interfacial morphology of MMMs, therefore, the present study provides brief description of the aforementioned interfacial (non-ideal) defects of MMMs and summarizes the techniques used to repair the interfacial defects for enhanced gas separation in MMMs. Â© 2014 Trans Tech Publications, Switzerland.